Impact of GST implementation on MSMEs- A Study with special reference to Bangalore City - N, Chaithra Y; Murthy, Dr. J.; Komma, Mr. Gowri Sankar (The journal of contemporary issues in business and government, 2022)
Goods and Services Tax (GST) is a comprehensive tax levy on manufacture, sale and consumption of goods and services at a national level. The GST regime holds an enormous opportunity for various sectors of the economy and is expected to herald a new era of indirect tax regime. By replacing various indirect taxes, GST is expected to be a key step in the field of indirect tax reform in India. The uniform tax reform under GST is expected to provide a uniform market for MSMEs. By cutting down multiple taxes, this reform will increase the flexibility in transfer of goods, hence reducing the total business cost. While the lower Goods and Services Tax (GST) rates may lead to a decline in inflation, economic growth may not improve significantly in the short term even though it will benefit both India Inc and the government in the medium term. Present study carried out in Peenya Industrial area, Banglaore city with a random sample of 110 responses. It’s concluded that there is significant relationship between dependent variable GST impacts on MSMEs.